ANALISIS PENGARUH STRUKTUR ASET, PERTUMBUHAN ASET, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Levina Aurelia, Herlin Tundjung Setijaningsih (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The aim of this research is to examine the effect of asset structure, asset growth and firm size to capital structure of manufacture companies listed on Indonesia Stock Exchange for the period 2014-2017. Sampe wasselected using purposive sampling method amounted to 91 companies. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 22. The result of this study show partially assets structure have significant effect to capital structurewhile asset growth and firm size have no significant impact to capital structure. However this study shows that simultaneously assets structure, assets growth and firm size have a significant effect on capital structure.